Jodhapura Rājya kī dastūra bahī - Rāṭhauṛa, Vikramasiṃha (Jodhapura : Rājasthānī Śodha Saṃsthāna, 1994)
Critical edition of a Rajasthani text on the social life and customs of Jodhpur (Princely State); includes a brief introduction.
Mode of access: Internet.
In Rajasthani; part in Hindi.
Keywords: Jodhpur (Princely State) -- Social life and customs